2019
DOI: 10.1038/s41598-019-53579-3
|View full text |Cite
|
Sign up to set email alerts
|

Paternal activation of CB2 cannabinoid receptor impairs placental and embryonic growth via an epigenetic mechanism

Abstract: The cannabinoid receptor type 2 (CB2) is the peripheral receptor for cannabinoids, involved in the homeostatic control of several physiological functions. Male mitotic germ cells express a high level of CB2, whose activation promotes their differentiation in both in vitro and in vivo experiments, controlling the correct progression of spermatogenesis. However, it remains elusive if CB2 activation in spermatogonia could affect reproductive success in terms of fertility and healthy pregnancy outcomes. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…In addition, an analysis of endocannabinoid system in rat testis during the first wave of spermatogenesis recently showed that CB 2 appears to be related to mitotic/meiotic stages (while CB 1 seems to be associated with spermatogonial stem cell activity) 32 . However, a study showed recently in young mice that the overactivation of CB 2 by a chronic administration of JWH133 decreases sperm count, increased sperm DNA methylation, impairs placental development, affects immune system, and reduces offspring growth via epigenetic alterations that can be transmitted to the next generation by spermatozoa 45 . Indeed, an appropriate concentration of CB 2 agonist was required in the present study for the in vitro model developed in mice to evaluate the yield of differentiate germ cell types.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an analysis of endocannabinoid system in rat testis during the first wave of spermatogenesis recently showed that CB 2 appears to be related to mitotic/meiotic stages (while CB 1 seems to be associated with spermatogonial stem cell activity) 32 . However, a study showed recently in young mice that the overactivation of CB 2 by a chronic administration of JWH133 decreases sperm count, increased sperm DNA methylation, impairs placental development, affects immune system, and reduces offspring growth via epigenetic alterations that can be transmitted to the next generation by spermatozoa 45 . Indeed, an appropriate concentration of CB 2 agonist was required in the present study for the in vitro model developed in mice to evaluate the yield of differentiate germ cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, paternal stress has been shown to affect a number of progeny phenotypes (50,51). There is also growing evidence that paternal epigenetic influences modify the development and maturation of the placenta and can thus lead to underweight progeny (52,53). (46,48,54).…”
Section: Discussionmentioning
confidence: 99%
“…Immune activation via polymicrobial abdominal sepsis in sires was shown to affect progeny immune phenotypes, accompanied by differentially hypo- and hyper-methylated cytosine residues spread over the sperm genome, implicating the sperm methylome as a potential carrier of epigenetic information (58). Further, paternal activation of CB2 cannabinoid receptor led to impaired placental and embryonic growth via altered DNA methylation/hydroxymethylation levels at imprinted genes in sperm (53).…”
Section: Discussionmentioning
confidence: 99%
“…Not only did exposed males have decreased sperm count, but their offspring demonstrated impaired placental development and reduced growth, compared to unexposed controls. This was accompanied by increased DNA methylation at the paternally expressed imprinted genes Peg 10 and Plagl1 in sperm, which was retained in the offspring placenta [ 15 ••]. Although the study highlights that overactivation of CBR2 can promote altered DNA methylation in sperm, which is retained in embryonic tissue and may cause altered offspring phenotypes, it could not confirm the precise effect that the epigenetic alterations may have on offspring.…”
Section: Pre-gestational Exposure To Cannabis: Epigenetic and Functiomentioning
confidence: 99%
“…In contrast, CBR2 is mainly expressed in immune cells. Male mitotic germ cells also express a high level of CBR2, whose activation promotes their differentiation and progresses spermatogenesis [ 15 ••]. During adolescence, the eCB system continues to facilitate neurodevelopment through its involvement in neuroplasticity and synaptic function.…”
Section: Introductionmentioning
confidence: 99%